Math, asked by sakshimense, 10 months ago

solve the factorization method
3x² - 2√6x + 2 = o​
plzzz answer me...

Answers

Answered by amritanishad1981
1

Step-by-step explanation:

Given: 3x

2

−2

6

x+2=0

3x

2

6

x−

6

x+2=0,

3

x(

3

x−

2

)−

2

(

3

x−

2

)=0

(

3

x−

2

)(

3

x−

2

)=0∴

3

x−

2

=0 or

3

x−

2

=0

3

x=

2

or

3

x=

2

,x=

3

2

or x=

3

2

So, the root is repeated twice, one for each repeated factor (

3

x−

2

)l.

∴ The two equal roots of 3x

2

−2

6

x+2=0 are

3

2

,

3

2

.

Answered by samyakjain648ggn
1

Answer:

hope you like this

Step-by-step explanation:

okay fine

Attachments:
Similar questions